(untitled) (UNED Research Journal, 2026)
Introduction: Otters (Lontra longicaudis) occur in both forested upper areas and disturbed middle and lower sections of the Peñas Blancas River basin in Costa Rica, with potential for zoonotic pathogen transmission to humans, domestic animals, and wildlife. Despite its ecological relevance as a top predator in freshwater ecosystems, information on viral infections affecting this otter remains scarce. Objective: To assess the presence of Influenzavirus A, Morbillivirus, and Coronavirus in this species and place. Methods: We collected 58 fecal samples from river rocks, confirmed them as L. longicaudis by endpoint PCR, and tested viral presence with RT-PCR. Conclusion: Although no viruses were detected, human-wildlife interactions warrant continued surveillance to prevent future outbreaks.